Feasibility studies and dynamics of catalytic liquid phase esterification reactions in a micro plant - Kulkarni, A. A.; Zeyer, K. -P.; Jacobs, T.; Kaspereit, M.; Kienle, Achim (Chemical Engineering Journal, 2008)
We present a new micro reactor concept which is suitable for investigations of heterogeneously catalyzed liquid phase reactions. In the set-up two reactants are mixed in a commercially available interdigital micro mixer. The outlet of the micro mixer is connected to a modular micro reactor that consists of stacked plates. Each plate contains a milled meandering channel filled with catalyst beads. By using a variable number of plates the residence time can be manipulated and thus adjusted for a specific task. The synthesis of butyl acetate is considered as a model reaction since it has been investigated in detail in conventional reaction systems. In a first step, some experimental results of the heterogeneously catalyzed reaction are presented. In the second part, the set-up is operated as a chromatographic reactor. Dynamic behaviour is investigated applying the frontal analysis mode and the elution chromatography mode. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: chromatographic reactor; heterogeneous catalysis; integrated process; modular micro reactor